2006
DOI: 10.1111/j.1442-2050.2006.00601.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in response of the proximal esophagus to wet swallows in patients of Chagas’ disease and idiopathic achalasia

Abstract: Chagas' disease and idiopathic achalasia have similar esophageal manifestations such as absent or incomplete lower esophageal sphincter relaxation and aperistalsis in the esophageal body (alterations seen mainly in the distal esophageal body). Our aim in this paper was to study the response of the proximal esophageal body to wet swallows in patients with Chagas' disease and patients with idiopathic achalasia. We retrospectively analyzed the time interval between the onset of the pharyngeal contractions 1 cm pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 24 publications
4
14
0
Order By: Relevance
“…The physiological system that controls esophageal contraction can function with some variability that does not cause symptoms. The amplitude and duration of contractions observed here in the proximal esophageal body were similar to our previous results obtained with normal volunteers (7,8,20) . The importance of the knowledge of these differences is to understand the possibility of different behaviours during drinking and eating and in the recovery from diseases which cause dysphagia.…”
Section: -Out/dez 2009supporting
confidence: 80%
“…The physiological system that controls esophageal contraction can function with some variability that does not cause symptoms. The amplitude and duration of contractions observed here in the proximal esophageal body were similar to our previous results obtained with normal volunteers (7,8,20) . The importance of the knowledge of these differences is to understand the possibility of different behaviours during drinking and eating and in the recovery from diseases which cause dysphagia.…”
Section: -Out/dez 2009supporting
confidence: 80%
“…In an investigation of the esophageal response to liquid swallows using the manometric method, we observed an increase in the time interval between the onset of pharyngeal contraction and the onset of the response of the proximal esophagus in chagasic patients compared to controls [11,12], showing a longer response latency of the proximal esophagus after swallowing. These patients take a longer time to ingest a liquid bolus [12].…”
Section: Discussionmentioning
confidence: 90%
“…Although studies on idiopathic achalasia have demonstrated a partial opening of the upper esophageal sphincter with increased residual pressure during swallow [23] , these features have not been fully demonstrated in Chagas' disease [12,13] . The time between pharyngeal contraction and proximal esophageal contraction (5 cm distance) after wet swallows in patients with megaesophagus is increased in Chagas' disease but not in idiopathic achalasia [24] . Contractions in the esophageal body are not of the same intensity, and tend to be more intense in patients with idiopathic achalasia [19,25] .…”
Section: Differences Between Idiopathic and Chagas' Disease Achalasiamentioning
confidence: 99%